ANALISIS MODAL KERJA DALAM MENILAI EFEKTIVITAS USAHA PADA KOPERASI KREDIT WAHANA ARTHA SELARAS BANDAR LAMPUNG - Yohanes Suharsana (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2011)
Management of working capital will be effective if used for working capital is sufficient in thesense according to need, no shortage and no excess. Therefore, working capital needs to bemanaged properly so that corporate objectives can be achieved.Sufficient working capital allows the company to operate as economical as possible andavoid the company of various problems arising from lack of capital, in addition to sufficient workingcapital to demonstrate the level of security available to creditors, especially short-term creditors.Management of working capital will be effective if used for working capital is sufficient in the senseaccording to need, no shortage and no excess. Therefore, working capital needs to be managedproperly so that corporate objectives can be achieved.